2015
DOI: 10.1038/srep07965
|View full text |Cite
|
Sign up to set email alerts
|

WS2 mode-locked ultrafast fiber laser

Abstract: Graphene-like two dimensional materials, such as WS2 and MoS2, are highly anisotropic layered compounds that have attracted growing interest from basic research to practical applications. Similar with MoS2, few-layer WS2 has remarkable physical properties. Here, we demonstrate for the first time that WS2 nanosheets exhibit ultrafast nonlinear saturable absorption property and high optical damage threshold. Soliton mode-locking operations are achieved separately in an erbium-doped fiber laser using two types of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
188
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 428 publications
(192 citation statements)
references
References 48 publications
3
188
1
Order By: Relevance
“…Recent studies have demonstrated that the sub-bandgap absorption in s-TMD nanoflakes can be saturated, and exploited this effect in the development of ultrafast lasers operating in the near-infrared, corresponding to photon energies in the range 0.6-1.12 eV. [7][8][9][10][11][12]15 While a growing body of experimental work continues to substantiate the process of sub-bandgap absorption in s-TMDs, and practical applications of this phenomenon are being leveraged in the field of photonics, theoretical analyses are limited and the origin of sub-bandgap optical absorption remains an open question. Here, we develop an analytical theory, testing the hypothesis of edge-mediated absorption in s-TMDs to explain the phenomenon of sub-bandgap saturable absorption.…”
Section: 16mentioning
confidence: 99%
“…Recent studies have demonstrated that the sub-bandgap absorption in s-TMD nanoflakes can be saturated, and exploited this effect in the development of ultrafast lasers operating in the near-infrared, corresponding to photon energies in the range 0.6-1.12 eV. [7][8][9][10][11][12]15 While a growing body of experimental work continues to substantiate the process of sub-bandgap absorption in s-TMDs, and practical applications of this phenomenon are being leveraged in the field of photonics, theoretical analyses are limited and the origin of sub-bandgap optical absorption remains an open question. Here, we develop an analytical theory, testing the hypothesis of edge-mediated absorption in s-TMDs to explain the phenomenon of sub-bandgap saturable absorption.…”
Section: 16mentioning
confidence: 99%
“…The new family of two-dimensional (2D) transition metal dichalcogenides materials, such as MoS 2 , WS 2 and WTe 2 , has attracted enormous interest nowadays due to their excellent optical response, [1][2][3][4] electronic control, [4][5][6] layer-number controlled electronic structure, [6][7][8] and extra valley degree of freedom 2, 9-12 etc. 13 Among them, research attention on MoSe 2 is rising because of its high photo-responsivity and tunable excitonic charges.…”
Section: Introductionmentioning
confidence: 99%
“…Pulses as short as 637 fs have been achieved with MoS 2 mode locked Er-based fiber lasers. 107 Using WS 2 , mode locking of Er 108 and Ho-Tm 109 doped fiber lasers has been successfully demonstrated, while MoSe 2 has been used to produce picosecond pulses with an Er-doped fiber laser system. 110 Other material structures have recently been introduced such as black phosphorous that has allowed the generation of pulses as short as 272 fs with an Er fiber laser 111 and from the new family of topological insulators that have recently been identified, that currently contain more [112][113][114] Consequently, there is a vast array of saturable absorbing species that can be used to mode lock fiber lasers each with distinct yet quite complementary properties.…”
Section: Other Two-dimensional Saturable Absorber Mode-locked Fiber Lmentioning
confidence: 99%